10+3x=5x+6

Simple and best practice solution for 10+3x=5x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+3x=5x+6 equation:


Simplifying
10 + 3x = 5x + 6

Reorder the terms:
10 + 3x = 6 + 5x

Solving
10 + 3x = 6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
10 + 3x + -5x = 6 + 5x + -5x

Combine like terms: 3x + -5x = -2x
10 + -2x = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
10 + -2x = 6 + 0
10 + -2x = 6

Add '-10' to each side of the equation.
10 + -10 + -2x = 6 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = 6 + -10
-2x = 6 + -10

Combine like terms: 6 + -10 = -4
-2x = -4

Divide each side by '-2'.
x = 2

Simplifying
x = 2

See similar equations:

| 5y=4x-6 | | -7.6=3.05 | | 491730x(16193649)=4 | | 6(x+2)=14x-16 | | 3a+4=3a+2+2 | | 3y+21x=15 | | 9+x^2=576 | | 3+7n=39 | | 5(t-3)+7t=6(2t+4)-11 | | 7+x=3x | | 9x^3-18x-95=0 | | 2(x^2-48)=x | | 2.6(x+1)=6(x+7.6) | | 3h+6=16 | | 27+2(x)=22.5+5(x) | | 9/10=x | | 2a+a+4=3a+5 | | (-a-5b+3)4ab= | | 8(4x-5)-7x=5(5x-8) | | -14x=70 | | 6(-6x+1)+6=12 | | PT=3x+4 | | -5(3m-4m)=5 | | -.75n=.024 | | 10n^2-10n-4=0 | | 3x+9-9=15 | | -.32m=.16 | | x=t-yz | | 4b-8-10=2b+6 | | 8(2x-4)=48 | | x-.21x=503.63 | | 3m^2+9m-4=0 |

Equations solver categories